Affordability of public pension benefit: a historical and empirical analysis of US state and local government pension contributions. (22nd September 2015) - PENG, JUN; WANG, QIUSHI
Abstract: As a result of the two severe stock market declines since 2000, there has been a steady debate about the affordability of state and local public pension benefits. We measured the affordability of pension benefits in terms of governments' ability to make the required contributions based on existing tax and revenue bases. We conducted a historical analysis of government pension contributions at national and state level over a 20-year period 1992–2011 and found that the real pension burdens have increased over this period. We also found substantial variation in pension burdens among the 50 states. The results of our empirical analysis showed that employee contribution share, investment return, size of the public workforce, and pension benefit level had significant effects on pension burdens. Based on these findings, we proposed several strategies for reducing pension burdens, including increasing employee pension contribution, reducing size of workforce, and improving pension investment performance.